Historical changes in epidemiology of diffuse panbronchiolitis - Kono, C.; Yamaguchi, T.; Yamada, et al., Y. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background and objective: Japanese pulmonologists, experienced in treating patients with diffuse panbronchiolitis (DPB) prior to the 1980s, have uniformly observed that new incidences of DPB are now a rare event in Japan. However, there is no epidemiological data to support this observation.We examined epidemiological trends of the number of patients with DPB in a large company. Design: The computerized health records of JR East Company employees were used to identify patients with DPB and then these were followed up using the assessments of these patients in JR Tokyo General Hospital and two other JR hospitals. The whole study period was 27 years (1976-2003), although detailed analyses were carried out for three specific periods; the first was 1976-1980, the second was 1989-1993, and the third was 1999-2003. Results: In the first period, 11 DPB cases (four incidence, and seven prevalence) were detected among a total of 355,572 workers. In the second period, three DPB cases (one incidence, and two prevalence) were identified from a total of 180,359 workers. In the third period, no case was found in a total of 144,485 workers. Conclusion: This epidemiological trend suggests that both the incidence and prevalence of DPB may have decreased.